Can challenge-based learning be effective online? A case study using experiential learning theory - Ruggero Colombari; Elettra D'Amico; Emilio Paolucci (CERN IdeaSquare Journal of Experimental Innovation, 2021)
The COVID-19 outbreak had a major effect on moving online learning activities, also traditionally experiential ones such as those designed upon Challenge-Based Learning (CBL) principles. This article explores the impacts produced on a Challenge-Based Innovation project work carried out in the context of a program developed by Politecnico di Milano and Politecnico di Torino. A survey of 92 students and interviews were carried out to assess the impact on learning outcomes and processes, and four main success factors were identified: informal interaction, time for exploration, asynchronous lecturing, relevant challenges. Suggestions for an effective design of online CBI-like programs are offered.